BATCH PROCESSING OF TREE-RING SAMPLES FOR RADIOCARBON ANALYSIS. Issue 1 (3rd February 2021) - Fogtmann-Schulz, Alexandra; Kudsk, Sabrina G K; Adolphi, Florian; Karoff, Christoffer; Knudsen, Mads F; Loader, Neil J; Muscheler, Raimund; Trant, Pernille L K; Østbø, Stine M; Olsen, Jesper
ABSTRACT: We here present a comparison of methods for the pretreatment of a batch of tree rings for high-precision measurement of radiocarbon at the Aarhus AMS Centre (AARAMS), Aarhus University, Denmark. The aim was to develop an efficient and high-throughput method able to pretreat ca. 50 samples at a time. We tested two methods for extracting α-cellulose from wood to find the most optimal for our use. One method used acetic acid, the other used HCl acid for the delignification. The testing was conducted on background 14 C samples, in order to assess the effect of the different pretreatment methods on low-activity samples. Furthermore, the extracted wood and cellulose fractions were analyzed using Fourier transform infrared (FTIR) spectroscopy, which showed a successful extraction of α-cellulose from the samples. Cellulose samples were pretreated at AARAMS, and the graphitization and radiocarbon analysis of these samples were done at both AARAMS and the radiocarbon dating laboratory at Lund University to compare the graphitization and AMS machine performance. No significant offset was found between the two sets of measurements. Based on these tests, the pretreatment of tree rings for high-precision radiocarbon analysis at AARAMS will henceforth use HCI for the delignification.